2005
DOI: 10.1196/annals.1345.038
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatitis C Virus Infection in Thalassemia

Abstract: Treatment of hepatitis C virus (HCV) in the general population has improved over the last decade. Patients treated with peginterferon alfa (PegIFN) and ribavirin (RBV) combination therapy demonstrate overall 50-55% sustained viral response (SVR) with rates as high as 80% in patients with genotypes 2 and 3. Because RBV induces hemolysis and subsequently increases blood transfusion requirements, combination therapy has been considered contraindicated for hemoglobinopathies. This report reviews the response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
3
6
0
1
Order By: Relevance
“…On the basis of the evidence-based data from randomized clinical trials, current treatment guidelines recommend administering this therapy for 48 weeks to patients infected by genotype 1 or 4, and for 24 weeks to patients infected by genotype 2 or 3. International guidelines recommend stopping antiviral therapy after 12 weeks in patients infected with genotype 1 or 4 if serum HCV-RNA levels have not decreased by at least 2 log units compared with baseline on the basis of strong evidence that such patients have a small likelihood of achieving sustained viral response after 48 weeks of treatment. 10 Descriptive studies [85][86][87][88][89] have reported data on small cohorts of thalassemia patients treated with ␣-interferon and ribavirin. The rate of SVR was more than 60%, but blood consumption increased during treatment by 30% to 60% because of ribavirin-associated hemolysis.…”
Section: Recommendations For Virologic and Clinical Evaluation Of Thamentioning
confidence: 99%
“…On the basis of the evidence-based data from randomized clinical trials, current treatment guidelines recommend administering this therapy for 48 weeks to patients infected by genotype 1 or 4, and for 24 weeks to patients infected by genotype 2 or 3. International guidelines recommend stopping antiviral therapy after 12 weeks in patients infected with genotype 1 or 4 if serum HCV-RNA levels have not decreased by at least 2 log units compared with baseline on the basis of strong evidence that such patients have a small likelihood of achieving sustained viral response after 48 weeks of treatment. 10 Descriptive studies [85][86][87][88][89] have reported data on small cohorts of thalassemia patients treated with ␣-interferon and ribavirin. The rate of SVR was more than 60%, but blood consumption increased during treatment by 30% to 60% because of ribavirin-associated hemolysis.…”
Section: Recommendations For Virologic and Clinical Evaluation Of Thamentioning
confidence: 99%
“…These results showed that the PEG-IFN-α plus RBV were effective in thalassaemic patients with HCV and moderate iron overload. Patients with thalassaemia and high iron overload can obtain a SVR after combination therapy, with rates that are similar to those in the general population and without significant complications [66]. Therefore, the combination of PEG-IFN-α plus RBV in patients with thalassaemia will also become standard therapy.…”
Section: Clinical Efficacy Of Ifn Therapy With Thalassaemic Patientsmentioning
confidence: 91%
“…[6][7][8] Butensky et al 7 treated 6 thalassemic patients with interferon, of whom only 1 patient (age 26 years) received peg-IFN plus ribavirin combination. In a recent study Harmatz et al 6 treated 21 patients of whom 16 completed the treatment.…”
Section: Other Similar and Contrasting Cases In The Literaturementioning
confidence: 99%